Estradiol metabolism by gut microbiota in women’s depression pathogenesis: inspiration from nature - Wei Zhang; Jinghan Jia; Yuhang Yang; Dawei Ye; Yan Li; Di Li; Jinxi Wang (Frontiers in Psychiatry)
The recurrence and treatment resistance of depression remain significant issues, primarily due to an inadequate understanding of its pathogenesis. Recent scientific evidence indicates that gut microbiota influence estradiol metabolism and are associated with the development of depression in nonpremenopausal women. Integrating existing studies on the regulation of estradiol metabolism by microorganisms in nature and the relevance of its degradation products to depression, recent scientific explorations have further elucidated the key mechanisms by which gut microbiota catabolize estradiol through specific metabolic pathways. These emerging scientific findings suggest that the unique metabolic effects of gut microbiota on estradiol may be one of the central drivers in the onset and course of depression in non-menopausal women.